Urgency and Strategy for Multicultural Education Transformation in Conflict Resolution: A Narrative Literature Review - M Sobry; Ismail; Abdul Fattah (International Journal of Education and Humanities, 2023)
This study examines the evolution of multicultural education in the context of conflict resolution. This study is guided by two central concerns: 1) the urgency of transforming multicultural education in conflict resolution, and 2) the strategy for transforming multicultural education in conflict resolution. This article is the result of a qualitative investigation employing a narrative literature study design. Google Scholar, an academic database, was used to compile all the literature. The authors used several document search keywords, namely “urgency, multicultural, education, resolution, conflict” and “strategy, multicultural, education, resolution, conflict”. This study clarified, first, that there are several imperatives for transforming multicultural education in conflict resolution: 1) understanding mutual respect; 2) increasing multicultural awareness; 3) developing dialogue skills; 4) encouraging social inclusion; 5) improving historical and contextual understanding; 6) developing conflict resolution skills; and 7) developing a pluralistic identity; Second, there are several strategies for transforming multicultural education in conflict resolution, such as 1) integration of multicultural principles into the educational curriculum; 2) training in conflict resolution skills; 3) dialogue education; 4) establishment of an inclusive learning environment; and 5) collaboration between communities. This research contributes conceptually to mapping educational institutions’ urgency and strategy to transform multicultural education into conflict resolution. This study contributes conceptually to the mapping of educational institutions' urgency and strategy to transition multicultural education into conflict resolution